2019
DOI: 10.2337/dc19-0152
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Hypoglycemic Effects of Hepatic-Directed Prandial Insulin: A 6-Month Phase 2b Study in Type 1 Diabetes

Abstract: Hepatic-directed vesicle insulin (HDV) uses a hepatocyte-targeting moiety passively attaching free insulin, improving subcutaneous insulin's hepatic biodistribution. We assessed HDV-insulin lispro (HDV-L) versus insulin lispro (LIS) in type 1 diabetes (T1D). RESEARCH DESIGN AND METHODSInsulin Liver Effect (ISLE-1) was a 26-week, phase 2b, multicenter, randomized, double-blind, noninferiority trial. RESULTSAmong 176 randomized participants (HDV-L n 5 118, LIS n 5 58), the difference in change from baseline A1C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
1
12
0
1
Order By: Relevance
“…Another attempt to design a hepato-preferential insulin are Hepatic Directed Vesicles (HDV), phospholipid-based 20-50 nm bicell disc carriers, that are aimed at delivering a proportion (e.g., 1%) of the injected insulin to the liver targeting biotin receptors on hepatocytes. In a phase 2 study over 26 weeks patients with type 1 diabetes were randomised 2:1 to either HDV-bound insulin lispro (HDV-L) or conventional insulin lispro (LIS) [22]. HDV-L achieved HbA1c noninferiority to conventional insulin lispro (LIS) without significant differences in insulin doses or times in hypoglycaemia (<24 mg/dl).…”
Section: Clinical Data Of Hepatic Directed Vesicles Bound Insulin Lispromentioning
confidence: 99%
“…Another attempt to design a hepato-preferential insulin are Hepatic Directed Vesicles (HDV), phospholipid-based 20-50 nm bicell disc carriers, that are aimed at delivering a proportion (e.g., 1%) of the injected insulin to the liver targeting biotin receptors on hepatocytes. In a phase 2 study over 26 weeks patients with type 1 diabetes were randomised 2:1 to either HDV-bound insulin lispro (HDV-L) or conventional insulin lispro (LIS) [22]. HDV-L achieved HbA1c noninferiority to conventional insulin lispro (LIS) without significant differences in insulin doses or times in hypoglycaemia (<24 mg/dl).…”
Section: Clinical Data Of Hepatic Directed Vesicles Bound Insulin Lispromentioning
confidence: 99%
“…Hepatic-directed vesicle (HDV) insulin is another insulin delivery system that contains biotin-phosphatidylethanolamine as a hepatocyte-targeting molecule in phospholipid bilayer vesicles [ 81 ]. In a phase 2b study of T1DM, HDV insulin lispro showed noninferior HbA1c lowering and no significant differences in hypoglycemia or insulin dosing compared with insulin lispro [ 82 ]. Further delineation of its efficacy and safety is awaited.…”
Section: The Future Of Insulin Therapy: Hepatopreferential Insulinsmentioning
confidence: 99%
“…However, this drug was associated with liver enzyme and lipid abnormalities, resulting in its discontinuation (29). Other emerging insulins are currently being engineered to resemble PegLispro without its side effects and include coupling insulin lispro with vesicles that confer hepatoselectivity (31,45).…”
Section: Hepatoselective Insulinmentioning
confidence: 99%